Porous hypercrosslinked polymer-TiO2-graphene composite photocatalysts for visible-light-driven CO2 conversion - Shaolei Wang (Nature Portfolio, 2019)
Renewable CO2 conversion to useful products presents a sustainable, carbon-neutral method to limit climate change, yet few materials can perform this complex chemistry. Here, authors prepare a polymer-TiO2-graphene composite that can take up CO2 and convert it to CH4 using light and water.